The Effect of Classical Music Therapy on Reducing Blood Sugar Levels in Wounded Patients with Foot Type Diabetes II in the Beautiful Wound Care Center Medan - Yuni Ramadhani; Sri Dewi Br Siregar; Jun Edy Samosir Pakpahan; Tri Widya Sari Ningsih (PT Inovasi Pratama Internasional, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder caused by the insulin hormone in the body that cannot be used effectively in regulating blood sugar balance, thereby increasing the concentration of sugar levels in the blood (hyperglycemia). Classical music therapy that provides a relaxing effect so that it can lower blood sugar levels. The purpose of this study was to identify the effect of classical music therapy on reducing blood sugar levels in patients with type 2 diabetes foot ulcers at Asri Wound Care Center Medan. This study uses a Quasy experimental research method, with a Pretest – Posttest Control Group Design, this research was conducted at Asri Wound Care Center Medan. The sample in this study was 40 respondents using the purposive sampling technique, the measuring instrument used was the Glucometer Easy Touch Glucose, Cholesterol, Uric Acid (GCU). The results of the Independent T - Test show that the P - Value is 0.000 because the P - Value is smaller than 0.05, it can be concluded that the classical music therapy method has a significant effect on reducing blood sugar levels. This can be proven by looking at the pretest and posttest which has shown a significant increase. this research can be expected to b useful information to improve the quality of education.